A simple scoring system to train surgeons in basic laparoscopic skills - Shepherd, Gregory; Kubiak, Rainer (Pediatric surgery international, 2016)
Aim: To develop and validate a scoring system for a training assessment tool using a box trainer which can objectively demonstrate progression in laparoscopic skills. Method: 170 assessments were performed over a 5-year period by doctors working in a busy paediatric surgical department. Each participant was scored based on experience and then undertook six laparoscopic tasks in a box trainer in a dry skills lab. The quicker and more accurate the performance, the lower the score. Validity and reliability tests were applied. Results: Pearson correlation coefficient demonstrated that more experienced surgeons performed better than novices with an r of -0.63 (p < 0.001). The mean assessment scores improved (reduced) with increasing experience score [4140 (0-20), 2696 (21-40), 1969 (>40) p < 0.001]. Improvement in score was seen at all experience levels with greatest improvement seen in the less experienced (2315, 1820, 1571 p < 0.001). Cronbach’s alpha was 0.70 and the intraclass correlation coefficient for test-retest reliability was 0.81. Conclusion: Construct validity with adequate reliability has been demonstrated for this simple training tool and scoring system. All experience levels demonstrated improvement in their laparoscopic skills by simulation training in a laparoscopic box trainer.